Evaluation of the astrometric capability of Multi-Channel Imager and simulated calculation of proper motion of M31 - Fang, Wenfeng; Yu, Yong; Peng, Xiyan; Yan, Zhaojun; Hao, Yanzhen; Shan, Huanyuan; Qi, Zhaoxiang; Liao, Shilong; Tang, Zhenghong; Wu, Qiqi; Fu, Zhensen (Frontiers in Astronomy and Space Sciences, 2024)
The Multi-Channel Imager (MCI), one of the back-end modules of the future China Space Station Telescope (CSST), is designed for high-precision space-based astronomical observations. This paper evaluates the astrometric capability of the MCI based on simulated observational images in the I, R and G bands and Gaia data: the M31 galaxy is selected as a representative case to validate the astrometric capability by calculating the proper motions (PMs) of the M31 member stars. In this analysis, positional uncertainty of 2.5 mas for brighter foreground reference stars from the Gaia DR3 catalog and of 7.5 mas for the fainter M31 member stars, are adopted respectively. We conclude that the precision of the MCI derived PMs strongly depends on the number of astrometric epochs per year. Specifically, uncertainty of 10 µas/yr is achievable with 10 epochs per year, and of 5 µas/yr with 50 epochs ignoring possible systematic effects.Symmetrically distributed fields yield better M31 kinematic parameters.